Abstraction in Traditional Kazakh Art - Samuratova, Tatigul (Journal of Urban Culture Research, 2025)
The objective of this study is to conduct an analysis of the main tendencies of abstract art in traditional Kazakh art, identify key characteristics and stages of abstraction evolution, and elucidate their impact on artists’ creativity. The research employed online surveys, questionnaires, data analysis, and organization. Statistical methods were applied to process and analyze the obtained data, including comparative analysis of mean values and calculation of t-indicators. The results of the statistical analysis indicate a statistically significant difference between the experimental and control groups at a significance level of 0.05. The t-statistic value (4.971) exceeds the critical t-value (1.98), allowing the rejection of the null hypothesis. This suggests that the use of graphic tablets and drawing software significantly influences the creative process in abstraction compared to traditional art methods employed by the control group.